Comparison of Lipid Fractions of Icteric Sample by Using Three Devices - Ummul Khair; Asvin Nurulita; Darwati Muhadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
COMPARISON OF LIPID FRACTIONS OF ICTERIC SAMPLE BY USING THREE DEVICES Ummul Khair1, Asvin Nurulita2,3, Darwati Muhadi2,31 Specialist Doctoral Education Program of Clinical Pathology Science, Faculty of Medicine, Hasanuddin University/RSUP Dr. Wahidin Sudirohusodo, Makassar 2 Department of Clinical Pathology Science, Faculty of Medicine, Hasanuddin University/RSUP Dr. Wahidin Sudirohusodo, Makassar3RSUP Dr. Wahidin Sudirohusodo, Makassar ABSTRACTIntroductionLipid fraction assessment in laboratory includes cholesterol, HDL, LDL, Triglycerides. The icteric sample is characterized by elevated levels of bilirubin and darkness yellow sample color. This research was to determine the comparison of lipid fraction of icteric sample by using three devices.MethodCross-sectional study at Clinical Pathology Laboratory of Dr. Wahidin Sudirohusodo of Makassar. Comparison of lipid fraction of icteric samples against 3 (three) devices (Pentra, Biomajesty, Conelab) in period April - June 2018. Statistical analysis using SPSS program.Result and Discussions Total sample of 50 indicated that cholesterol level by Biomajesty was lower than Pentra400 (p < 0.001), while the cholesterol level by Conelab was significantly lower than Pentra400 (p > 0.001), but not significantly different with Biomajesty (p < 0.05). HDL level by Biomajesty did not differ significantly with Pentra400 (p > 0.05). HDL level by Conelab were significantly lower than Pentra400 (p < 0.001) and Biomajesty (p < 0.01). HDL level by Biomajesty was smallest than Pentra and Conelab. LDL level by Biomajesty did not differ significantly with Pentra400 (p > 0.05) while LDL level by Conelab was significantly lower than Pentra400 (p < 0.001) and Biomajesty (p < 0.001). It can be seen that the range of TG by Biomajesty is smallest (more accurate) than Pentra400 and Conelab. TG level by Biomajesty was significantly lower than Pentra400 (p < 0.01) while TG level by Conelab was not significantly different than Pentra400 (p > 0.05), but it was significantly higher than Biomajesty (p < 0.001).Conclusion and RecommendationThe research shows that Biomajesty is an accurate device for the measurements of HDL, LDL, and TG of icteric samples, whereas Conelab is an accurate device for cholesterol measurement of icteric samples.KeywordsLipid fraction, icteric sample, Pentra, Biomajesty, Conelab